Assessing the critical success factors for the sustainable construction project management of Saudi Arabia - Abdullah Alghuried (Journal of Asian Architecture and Building Engineering)
The construction sector in Saudi Arabia faces significant challenges in achieving sustainability in project management, encompassing activities from design to project completion. This research aims to identify and evaluate the critical success factors (CSFs) essential for sustainable construction project management in Saudi Arabia. Through an extensive literature review, 24 CSFs were identified, reflecting the sector’s complex dynamics. A detailed survey of industry experts assessed the importance of these factors using a Likert scale, with further analysis conducted through the Relative Importance Index (RII) and Analytic Hierarchy Process (AHP). The CSFs were categorized into five groups: human resources and stakeholder requirements, sustainable project delivery and stakeholder engagement, strategic planning and alignment, project management practices and leadership, and compliance and governance. Stakeholders emphasized the adoption of modern tools and processes to overcome challenges and improve project outcomes. The study highlighted five key CSFs: effective strategic planning, adherence to anti-corruption measures, efficient resource allocation, project managers’ expertise, and robust policy enforcement. These factors are pivotal in advancing sustainable construction project management in Saudi Arabia. The study provides a structured framework for evaluating CSFs and offers practical insights to stakeholders for promoting sustainability within the construction sector, particularly in Saudi Arabia and the Middle East.